SODIUM DODECYL SULFATE-POLYACRYLAMIDE GEL ELECTROPHORESIS AS A USEFUL TOOL FOR ASSESSING THE SEVERITY OF DIABETIC NEPHROPATHY - Kostovska, Irena; Labudovic, Danica; Tosheska-Trajkovska, Katerina; Bogdanska, Jasna; Topuzovska, Sonja; Ampova, Hristina; Brezovska Kavrakova, Jilijana; Cekovska, Svetlana (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Proteinuria is a hallmark of diabetic nephropathy (DN). Qualitative analysis of proteinuria plays an important role in the diagnosis and prognosis of DN. SDS-PAGE is the most frequently used method for qualitative analysis of proteinuria.The aim of this study was to test the significance of SDS-PAGE of urinary proteins in assessing the severity of kidney disease in DN patients by comparing the results of kidney laboratory tests among different proteinuric DN patients. 92 confirmed cases of DN were included in this study. Urinary protein separation was performed using ultrathin horizontal gradient linear (4-22%) SDS-PAGE. According to the type of proteinuria all patients were categorized into three groups: patients with glomerular, patients with tubular, and patients with mixed proteinuria. In all patients were estimated urinary microalbumin to creatinine ratio (UMCR) and glomerular filtration rate (GFR). Blood serum was used for biochemical analyses. SDS-PAGE analysis showed that 50% of studied DN patients have mixed type of proteinuria. UMCR and serum creatinine were significantly increased, while eGFR was significantly decreased in patients with mixed proteinuria compared to patients with glomerular or tubular proteinuria (p<0.001). We found a significant difference between patients with mixed proteinuria and patients with glomerular or tubular proteinuria regarding the duration of disease and glycaemic control (p<0.001). DN patients with mixed proteinuria have a significant decline in kidney function than those who excrete glomerular or tubular proteins only. SDS PAGE is a good noninvasive tool for assessing the severity of DN. Key words: SDS-PAGE, diabetic nephropathy, proteinuria   https://doi.org/10.55302/JMS2251020k